Declining Fitness Levels are a Challenge to Well-Being in Finland – effective actions to increase physical activity and reverse the downward spiral of fitness - Vasankari, Tommi; Tapio, Petri; Ahokas, Ira; Kokko, Sami; Helminen, Ville; Heikinheimo, Vuokko; Hurmerinta, Leila; Lyytimäki, Jari (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2023)
The physical functional capacity of Finns has been declining for decades: • The number of young men entering military service with poor physical fitness has increased eightfold • The number of men with poor muscle fitness has increased manifold • The average weight of new recruits has increased by 8 kg • The results of the MOVE! measurements of schoolchildren show the same alarming trend also in schoolchildren. As a result of the prolonged negative trend described above, the physical fitness of Finns of working age will continue to deteriorate significantly also in the coming decades. By 2040, according to a very conservative forecast, only very few people aged 50 or over in Finland will be in good physical fitness. This vicious cycle will lead to an increasing incidence of non-communicable diseases (such as type 2 diabetes, depression, cardiovascular diseases, musculoskeletal diseases, etc.). Being ill leads to increased sickness absences, earlier disability, and lower labour productivity. Unless this negative trend can be reversed, we will not be able to extend working life, the economic backbone of the state, municipalities, and cities will be broken, and the base of the national defence (the reserve army) will not hold up. The steady decline in fitness and increase in obesity will cause problems across all sectors of government. No amount of economic growth will be enough if the downward spiral of the physical functional capacity and fitness of working-age Finns is not reversed. We need multiple, simultaneous, effective measures across all sectors, at the national as well as the local level. These simultaneous, multi-sectoral actions require strong leadership and coordination between different sectors. Therefore, at the national level, the Prime Minister's Office and, at the local level, the municipal or city management group, are capable actors to lead these simultaneous measures that are needed across sectors of government. Effective measures are needed for those in the working life today who are struggling with their physical functional capacity, as well as to ensure the functional capacity of the workforce in the future. This policy brief is the second in its series from the Healthy Lifestyles to Boost Sustainable Growth (STYLE) project, combining interdisciplinary knowledge on trends in transport and physical activity. Interpreting them through infrastructure and service designs and changing lifestyles, we generate insight on novel business opportunities and intervention models that induce physical activity. This provides innovative pathways towards current national policy targets and promotion of the societal vision. The project is funded by the Strategic Research Council at the Academy of Finland. Read more: www.styletutkimus.fi/en